Prognosis of Hepatic Encephalopathy on Discharge in A Tertiary Level Hospital (The Planet, 2023)
Introduction: Hepatic encephalopathy (HE) is a frequent complication of cirrhosis and a major public health problem. It is assumed that approximately 60-80% of patients with liver cirrhosis develop hepatic encephalopathy. The study aimed to see the prognosis of hepatic encephalopathy on discharge in a tertiary-level hospital. Methods: This prospective observational study was conducted at the Department of Medicine in Combined Military Hospital (CMH), Dhaka, Bangladesh for 6 months. A total of 50 subjects were included in this study. Result:In this study, nearly three- a fifth (58%) of the patients exhibited HBsAg, 20% had Anti HCV antibody, 6% Anti-HBc, and 14% had Non-HBV. Repeated measure ANOVA analysis revealed that the improvement of the patients in terms of these variables was highly significant (p
Keywords: Hepatic Encephalopathy; West Haven Criteria; Cirrhosis; Prognosis